ARSTUDIO. Estúdio Virtual para Produção de Conteúdos Audiovisuais em Realidade Aumentada para TV Digital - Sementille, Antonio Carlos; Américo, Marcos; Rolfsen Belda, Francisco; Marar, João Fernando; Kizzy Cunha, Arielly (Facultad de Periodismo y Comunicación Social, 2018)
“Virtual Studio” is a system developed for the creation of virtual sets, as well as any three-dimensional virtual objects that can be digitally integrated to the scenes captured on a real television studio. Through techniques such as chroma-key, computer graphics , augmented reality and virtual reality is possible flexibility in producing content for digital TV, reduce cost and meet 12.485/2011 law, the Brazilian “Law of Pay TV”, which has among its objectives “to increase the production and circulation of diverse and quality Brazilian audiovisual content, generating jobs, income, royalties, professionalism and strengthening of national culture” (ANCINE , Brazilian Nacional Cinema Agency ). Based on this background, an overview of the benefits of using the technologies mentioned for the production of content for digital television is presented. This work involves the development of a system of Interactive Virtual Studio called ARSTUDIO per team of researchers from the Posgraduate Program in Digital Television: Information and Knowledge at UNESP, São Paulo State University in Bauru, State of São Paulo, Brazil.